A Transparent Nanopatterned Chemiresistor: Visible‐Light Plasmonic Sensor for Trace‐Level NO2 Detection at Room Temperature. Issue 20 (4th April 2021) - Lim, Kyeorei; Jo, Young‐Moo; Yoon, Ji‐Wook; Kim, Jun‐Sik; Lee, Dong‐Jae; Moon, Young Kook; Yoon, Ji Won; Kim, Jae‐Hyeok; Choi, Hun Ji; Lee, Jong‐Heun
Abstract: The highly selective detection of trace gases using transparent sensors at room temperature remains challenging. Herein, transparent nanopatterned chemiresistors composed of aligned 1D Au–SnO2 nanofibers, which can detect toxic NO2 gas at room temperature under visible light illumination is reported. Ten straight Au–SnO2 nanofibers are patterned on a glass substrate with transparent electrodes assisted by direct‐write, near‐field electrospinning, whose extremely low coverage of sensing materials (≈0.3%) lead to the high transparency (≈93%) of the sensor. The sensor exhibits a highly selective, sensitive, and reproducible response to sub‐ppm levels of NO2, and its detection limit is as low as 6 ppb. The unique room‐temperature NO2 sensing under visible light emanates from the localized surface plasmonic resonance effect of Au nanoparticles, thereby enabling the design of new transparent oxide‐based gas sensors without external heaters or light sources. The patterning of nanofibers with extremely low coverage provides a general strategy to design diverse compositions of gas sensors, which can facilitate the development of a wide range of new applications in transparent electronics and smart windows wirelessly connected to the Internet of Things. Abstract : Transparent and visible light‐activated NO2 sensor that can operate at room temperature is presented. The pattern of Au–SnO2 nanofibers with extremely low coverage fabricated by direct‐write near‐field electrospinning exhibits high transparency (≈93%), ultrahigh response to NO2, and reversible sensing behaviors under visible light or natural sunlight, enabling the ppb‐level monitoring of indoor or outdoor NO2 .